2014
DOI: 10.1002/ppap.201400114
|View full text |Cite
|
Sign up to set email alerts
|

On the Plasma Chemistry During Plasma Enhanced Chemical Vapor Deposition of Microcrystalline Silicon Oxides

Abstract: The advanced opto‐electronic properties of microcrystalline silicon oxide (µc‐SiOx:H) thin film layers deposited by means of plasma enhanced chemical vapor deposition (PECVD) resulted in several applications of this material especially in solar cells and modules in the last years. We investigated the plasma chemistry during the PECVD of µc‐SiOx:H using in situ plasma diagnostics. Plasma properties are related to the properties of resulting µc‐SiOx:H films measured ex situ. Two different deposition regimes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
5
20
0
Order By: Relevance
“…The individual contributions of these two phases provide a straightforward way to tune the optoelectronic properties of nc-SiO X :H. However, during the PECVD deposition of nc-SiO X :H many parameters like pressure, power, frequency and the individual gas flows can be varied, all of which affect the properties of the deposited thin films. Consequently, much research has been devoted to achieve the optimum trade-off between the conductivity and the optical properties of the material [5,[8][9][10] by tuning the deposition conditions. In this paper, we developed a microstructure model based on numerous n-and p-doped nc-SiO X :H films that were deposited under various deposition pressures, plasma powers, plasma frequencies and gas mixtures to provide guidelines for a systematic classification of nc-SiO X :H by establishing a link between the structure of the deposited films and the optoelectronic performance of nc-SiO X :H. This classification helps to identify the structure of the deposited nc-SiO X :H material and provides hints for further optimization steps.…”
Section: Introductionmentioning
confidence: 99%
“…The individual contributions of these two phases provide a straightforward way to tune the optoelectronic properties of nc-SiO X :H. However, during the PECVD deposition of nc-SiO X :H many parameters like pressure, power, frequency and the individual gas flows can be varied, all of which affect the properties of the deposited thin films. Consequently, much research has been devoted to achieve the optimum trade-off between the conductivity and the optical properties of the material [5,[8][9][10] by tuning the deposition conditions. In this paper, we developed a microstructure model based on numerous n-and p-doped nc-SiO X :H films that were deposited under various deposition pressures, plasma powers, plasma frequencies and gas mixtures to provide guidelines for a systematic classification of nc-SiO X :H by establishing a link between the structure of the deposited films and the optoelectronic performance of nc-SiO X :H. This classification helps to identify the structure of the deposited nc-SiO X :H material and provides hints for further optimization steps.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because alloying of silicon with oxygen allows to increase the optical gap energy and enhance corresponding transparency of the material and to adjust the refractive index over a considerable range. μc‐SiO x :H is a phase mixture of microcrystalline silicon (μc‐Si:H) and amorphous silicon oxide (a‐SiO x :H) and can be doped p‐type as well as n‐type, making µc‐SiO x :H a versatile material for applications such as window layer, intermediate reflector, and/or back reflector in silicon solar cells .…”
Section: Introductionmentioning
confidence: 99%
“…20 In addition to the [O]/[Si] ratio dependence of the filament formation, different approaches to tune the crystallinity were investigated, such as the influence of the hydrogen dilution 21 and the PECVD pressure. [22][23][24] Recent studies have also shown that the refractive index and conductivity can be tuned almost independently of each over a wide range. 25 The nanocrystalline silicon growth during PECVD is usually explained by the competition and/or interaction of three distinct mechanisms.…”
Section: Introductionmentioning
confidence: 99%